On Using of a Mobile Learning in Teaching History at UIN Imam Bonjol Padang: A Research and Development Model - Sasmi Nelwati; Rezki Amelia (AT-TA'LIM, 2019)
The study aims to develop a learning model through mobile learning in the Social Sciences Department of Tarbiyah Faculty of UIN Imam Bonjol Padang. This research is a developmental research. This research is aimed at developing a mobile learning model that is expected to be able to produce a product in the future. The product produced is in the learning development model through mobile learning in the Social Sciences Department of Tarbiyah Faculty of UIN Imam Bonjol Padang. Based on the results of the study, it was found that the development of learning models through mobile learning in the Social Sciences Department of History of the Faculty of Tarbiyah and Teacher Training at UIN Imam Bonjol Padang was effective in increasing students' interest in Social Sciences Department History and Development of practical learning models through mobile learning developed in Social Studies Department History of the Faculty of Tarbiyah and Teaching UIN Imam Bonjol Padang deserves to be developed in order to improve the quality and interest of students in the learning process.